PERTANGGUNGJAWABAN PIDANA PENYALAHGUNAAN NARKOBA YANG DILAKUKAN OLEH WARGA NEGARA ASING - Sutrisna, M. Dody; Mertha, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013)
Drugs abuse which doing by foreigner is increasingly happen in Indonesia andits become a threat for National Security. Firm and consistent rules are needed in copewith of drug abuse by foreigner. Criminal responbility for foreign should do inmaximum way by given criminal sanctions. In other way, firm criminal sanctions fordrug user especially doing by foreigner can give leery effect and uphold nationalsovereignity.
Keywords: drug, responbility, abuse, community foreigner.